Public Mask Versus Inner Darkness: An Analysis of Persona and Shadow in “Taxi Driver” (1976) Movie - Mulyadi; Robby Satria (INTERACTION: Jurnal Pendidikan Bahasa, 2026)
Travis Bickle in Taxi Driver (1976) exhibits increasingly unstable behavior marked by social withdrawal, moral obsession, and escalating violence, raising questions about the psychological forces behind his breakdown. This study examines the Persona and Shadow of Travis which influence his behavior and eventual breakdown. Although the film and Jungian theory have been widely discussed, Travis Bickle’s psychological development has not been systematically examined through the interaction of Carl Jung’s Persona and Shadow archetypes, resulting in a limited understanding of his inner conflict. This study employs a qualitative design using library research, with the film as primary data and scholarly works on Jungian psychology and film analysis as secondary sources. Data were collected through close and repeated viewing, focusing on key scenes, character behavior, and visual symbolism related to the Persona and Shadow, and analyzed descriptively through thematic categorization. The findings indicate that Travis’ Persona is reflected in his attempts to remain polite and socially functional, while his Shadow manifests as repressed anger and moral hostility. As social rejection and isolation intensify, the tension between these aspects leads to psychological instability and violence. This study demonstrates the usefulness of Jung’s archetypal theory in explaining psychological conflict and character development in film narratives.